MANAJEMEN LABA: PRO-KONTRA PEMAKNAAN ANTARA KREDITUR DAN DEBITUR DALAM PROSES PEMBIAYAAN KREDIT - Anggie Febriyanti; Tjiptohadi Sawarjuwono; Bram Ade Pratama (Jurnal Manajemen dan Wirausaha, 2014)
Earnings management has been a hot topic. As long as along with the Indonesian Financial Accounting Standard, this cannot be considered as earnings management. However, the accountants tend to apply the particular treatment to meet their specific interests. The creditors do not consider whether there is earnings management, but they will apply many other more comprehensive evaluation techniques. This study applied unobtrusive observation. By doing this, the researchers were able to uncover the existing earnings management as well as the variety of debtors’ and creditors’ considerations.